Dynamic Failure Mode and Dynamic Response of High Slope Using Shaking Table Test - Zhijun Zhou; Chenning Ren; Guanjun Xu; Haochen Zhan; Tong Liu (Shock and Vibration)
A shaking table test was performed to study the dynamic response and failure modes of high slope. Test results show that PGA amplification coefficients increased with increasing elevation and the PGA amplification coefficient of the concave slope was slightly larger than that of the convex slope. The slope type affected the dynamic response of the slope. The elevation amplification effect of the concave slope under seismic load was more significant than that of the convex slope; thus, the concave slope was more unstable than the convex slope. Additionally, the PGA amplification coefficient measured on the slope surface was always larger than that inside the slope, and the data show an increasing trend with the broken line. The dynamic amplification effect of the high slope was closely related to the natural frequency of the slope. Within a certain range, the higher the frequency, the more significant the amplification effect. The dynamic failure process of concave and convex slopes was studied through tests. Findings indicate that the dynamic failure modes of the concave slope are characterized by shoulder collapse, formation of the sliding surface, and integral sliding above the slope line. Dynamic failure modes of the convex slope are mainly slips in the soil layer and collapse of the slope near the slope line.